RANCANGAN MODUL PEMBELAJARAN BIOPESTISIDA AIR KULIT JERUK NIPIS PADA KONSEP BIOTEKNOLOGI SMA KELAS XII - Yuci, Puteri; Darmawati, Darmawati; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The research was done to use the results of research that affect the grayak caterpillar skin concentration (Citrus aurantifolia) as a biopestithe grayak (Spodoptera litura) bug in the spinneret plant (Amaranthus tricolor) in the design of the biochemical materials study module in April 2020. The study was conducted with a two-stage analysis and design design. The study is being done in the school of teachery and education of the new pekanbaru university. Based on analysis of potential research results can be used asa design module for the xii class of high school biotech concept at kd 3.10 analyzing the principles of bioengineering and its application as an effort to increase human welfare and kd 4.10 presented a report based on scientific method for the application of experimental principles of conventional biotechnology. The module's design development covers a level of analysis and design with a module structure that consists of a cover, the preface, the table of contents, the curriculum level, module use instruction, introduction, learning activities, exercises, summary, formative test, feedback, follow-up, follow-through, formative test answers, library and glossary listsKey Words: Biopesticide module, Citrus aurantifolia, Spodoptera litura, Amaranthus tricolor